Hemithioindigo-Based Trioxobicyclononadiene: 3D Multiswitching of Electronic and Geometric Properties - Kohl, Fabien; Gerwien, Aaron; Hampel, Frank; Mayer, Peter; Dube, Henry (Journal of the American Chemical Society, 2021)
Molecular photoswitches that offer simultaneous precise control over geometrical and electronic changes are rare yet highly sought tools for the development of responsive nanosystems. Here we present such an advantageous combination of property control within a novel multiphotoswitch architecture. Hemithioindigo-based trioxobicyclononadiene (HTI-TOND) offers a rigid three-dimensional molecular structure that undergoes different exotic rearrangement reactions upon photochemical and thermal signaling. Three to four different states with distinct geometric and electronic properties can be accessed reversibly in high yields within this molecular framework. Thus, a highly promising and unique switching tool has become available to instill the next level of addressability at the smallest scales.
CRIS-Team Scopus Importer:2022-03-04